ACADEMIC LEADERSHIP IN THE CONTEXT OF NEOLIBERALISM: The Practice of Social Work Directors - Barnoff, Lisa; Moffatt, Ken; Todd, Sarah; Panitch, Melanie (Canadian Social Work Review / Revue canadienne de service social, 2017)
Driven by neoliberal principles, new managerialist demands for austerity and accountability are reshaping the practices of directors of Canadian schools of social work. In this paper, we discuss research that aimed to clarify how directors of social-justice-oriented social work schools engage in academic leadership in the context of new managerialism. We were especially interested to know how this engagement affects them. Our data come from five interviews and one focus group with five directors of schools of social work in Canada. Four themes emerged from the data: directors’ fight for resources; directors as agents for resource management; directors as ‘buffers’ to shield their faculty from stresses associated with resource cuts; and resistance through relationship-building. Pushed to act as resource managers, directors’ efforts are largely unknown and sometimes unappreciated by faculty members. Our findings will be useful to professional schools negotiating their future in the university system, especially at a time when social work faculties struggle to motivate individuals to take on leadership roles. Overall, the findings of this study help clarify the nature of leadership practices in schools of social work, contributing to a better understanding of the current situation, the requirements of leadership, and how to support leadership.